COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF THE START AND CTAS TRIAGE SYSTEMS IN DISASTER MANAGEMENT IN EMERGENCY DEPARTEMENT: A SYSTEMATIC LITERATURE REVIEW : DISASTER MANAGEMENT - Wahyu Ade Wardani; Al Mohades; Zaqyyah Huzaifah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Emergency departments (ED) are often overwhelmed during mass casualty incidents (MCI). The trade-off between the speed of Simple Triage and Rapid Treatment (START) and the accuracy of the Canadian Triage and Acuity Scale (CTAS) poses a management dilemma. This study aims to evaluate and compare the effectiveness of START and CTAS in ED. Methods: A systematic literature review (SLR) was conducted using the PRISMA guidelines. Sixteen publications from PubMed, Google Scholar, ScienceDirect, and PMC were evaluated with five main articles analyzed for direct comparison. Results: The study shows that START is proven to be much faster (average of 33 seconds/patient) with high sensitivity in critical patients but has a high risk of under triage, whereas CTAS takes longer (138 seconds/patient) but excels in clinical accuracy and resource allocation precision. There is no single ideal instrument for MCI. Conclusion: The implementation of a dual triage model using START at the ED entrance followed by CTAS in the care area is highly recommended to optimally balance response speed and patient safety.